2010
DOI: 10.1007/s00464-010-1328-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and cost-effectiveness of common laparoscopic procedures

Abstract: This study demonstrated the superiority of laparoscopy over conventional open surgery across all illness severity risk groups for common surgical procedures. The results in general show that laparoscopic surgery is safe, efficacious, and cost-effective compared with open surgery and suggest that laparoscopic surgery should be the procedure of choice for all common surgical procedures, regardless of illness severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 36 publications
0
57
1
2
Order By: Relevance
“…Patients in our study showed excellent results in terms of postoperative complications, pain and length of stay. About postoperative pain, all procedures positively compared with wellanalyzed series describing these procedures performed by conventional laparoscopy [1]. Also, SILS appendectomies and cholecystectomies had a similar length of stay than previously published laparoscopic results [2] [3].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Patients in our study showed excellent results in terms of postoperative complications, pain and length of stay. About postoperative pain, all procedures positively compared with wellanalyzed series describing these procedures performed by conventional laparoscopy [1]. Also, SILS appendectomies and cholecystectomies had a similar length of stay than previously published laparoscopic results [2] [3].…”
Section: Discussionmentioning
confidence: 75%
“…One of the main critical issues when introducing a new surgical technique is patient safety, which can be elucidated from the need to convert to a conventional laparoscopic or open procedure because of intraoperative problems [1]. The majority of patients in our study completed their procedure without the need of adding supplemental ports or converting to open surgery, showing that SILS introduction in a procedural stepwise manner is associated with a low rate of intraoperative problems.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The benefits of laparoscopic or minimally invasive surgery (better cosmesis, reduced postoperative pain, and faster recovery) are well known for many diseases, but reduced trauma to the abdominal wall is particularly evident in pancreatic surgery. [1,2] However, surgery of the pancreas is still challenging, and although the first reported case of laparoscopic approach in pancreatic disease was in 1994, it has been widely applied only in the past decade. [3][4][5] Open surgery is still performed because of the anatomy of pancreas, limitations of team skills, and some early concerns regarding oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Even after almost 20 years of consecration of the method in Brazil, laparoscopic surgery is not covered by SUS for bariatric surgery. Several studies have demonstrated the highest efficiency and the lowest complication rate for this method 13,14 . In addition, it has been shown that the higher initial cost of laparoscopic surgery is offset by the savings in spending on length of stay, complications and readmissions and concluded that all respondents prefer the laparoscopic approach, believing that there would be more operations compared with laparotomy.…”
mentioning
confidence: 99%